Endodontic Management of a Maxillary First Molar with Taurodontia and Two Palatal Canals: A Case Report - Sahib, Ali Muneer; Ghabraei, Sholeh (Iranian Endodontic Journal, 2021)
The present case report describes an endodontic treatment of a three-rooted maxillary first molar with taurodontia and a palatal root with two separate canals. Maxillary first molar with two palatal canals is rare since extra canals are found most in the mesiobuccal root as the second mesiobuccal canal. Clinicians should have a thorough knowledge of the root canal system and internal anatomy and be alert about the possible existence of any variation in the canal morphology because it determines the successful outcome of an endodontic treatment.